Global folate status in women of reproductive age: a systematic review with emphasis on methodological issues. Issue 1 (21st September 2018) - Rogers, Lisa M.; Cordero, Amy M.; Pfeiffer, Christine M.; Hausman, Dorothy B.; Tsang, Becky L.; De‐Regil, Luz María; Rosenthal, Jorge; Razzaghi, Hilda; Wong, Eugene C.; Weakland, Aliki P.; Bailey, Lynn B.
Abstract: Inadequate folate status in women of reproductive age (WRA) can lead to adverse health consequences of public health significance, such as megaloblastic anemia (folate deficiency) and an increased risk of neural tube defect (NTD)‐affected pregnancies (folate insufficiency). Our review aims to evaluate current data on folate status of WRA. We queried eight databases and the World Health Organization Micronutrients Database, identifying 45 relevant surveys conducted between 2000 and 2014 in 39 countries. Several types of folate assays were used in the analysis of blood folate, and many surveys used folate cutoffs not matched to the assay. To allow better comparisons across surveys, we attempted to account for these differences. The prevalence of folate deficiency was >20% in many countries with lower income economies but was typically <5% in countries with higher income economies. Only 11 surveys reported the prevalence of folate insufficiency, which was >40% in most countries. Overall, folate status data for WRA globally are limited and must be carefully interpreted due to methodological issues. Future surveys would benefit from using the microbiologic assay to assess folate status, along with assay‐matched cutoffs to improve monitoring and evaluation of folic acid interventions, thus informing global efforts to prevent NTDs. Abstract : Inadequate folate status in women of reproductive age (WRA) can lead to adverse health consequences of public health significance, such as megaloblastic anemia (folate deficiency) and an increased risk of neural tube defect (NTD)‐affected pregnancies (folate insufficiency). Our review aims to evaluate current data on folate status of WRA. We queried eight databases and the World Health Organization Micronutrients Database, identifying 45 relevant surveys conducted between 2000 and 2014 in 39 countries.